CEOS, AUTHORS AND WHITE COLLAR WORK. - Laird, Benjamin (Overland)
The article presents the author's insights on several chief executive officers (CEOs), authors and white-collar workers. The author pays tribute to the success of Apple Inc. CEO Steve Jobs in developing new technologies. Moreover, the author comments on the role of white-collar intellectual workers in achieving corporate success.